ANALISIS KESALAHAN SISWA MENYELESAIKAN SOAL DINAMIKA ROTASI BERDASARKAN PROSEDUR NEWMAN DI SMA NEGERI 7 PONTIANAK - Adi Rajiman; Tomo Djudin; Erwina Oktavianty (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the profile and causes of students' errors in solving Rotation Dynamics questions based on Newman procedures at SMAN 7 Pontianak. This research is a descriptive qualitative research. The data collection technique uses description questions. Then interviews with students who have been selected to be research subjects. The data analysis of this research was carried out by means of data reduction, data presentation and verification. The results showed that (1) none of the research subjects read wrongly, (2) errors in understanding were made by the students as much as 37.5%, (3) errors in the transformation made by the students were 21.875%. (4) errors in the processing ability made by students were 3.125%, (5) errors in writing answers made by students were 6.25%. The results of the analysis of students' errors in solving the Rotation Dynamics questions based on the Newman procedure showed that students experienced the most errors in understanding the problem, namely 37.5%. So it is hoped that the results of this study can be used to improve students' understanding in solving questions.